ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION IN FANCONI ANEMIA; A SINGLE CENTRE EXPERIENCE - Tariq Azam Khattak; Muhammad Farhan; Tariq Ghafoor; Tariq Mahmood Satti; Qamar Un Nisa Chaudhry; Mehreen Ali Khan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the treatment outcome of Hematopoietic stem cell transplantation in Fanconi Anemia. Study Design: Case series. Place and Duration of Study: Armed Forces Bone Marrow Transplant Center, Rawalpindi, from Jan 2001 to Jun 2018. Methodology: Data of all Fanconi anemia patients who had fully HLA matched bone marrow transplant during this period was analysed for variables affecting the outcome in terms of overall survival. Those fanconi anemia patients who had myelodysplastic changes or acute myeloid leukemia were excluded. Results: Total 27 patients underwent fully HLA matched allogeneic bone marrow transplant for Fanconi Anemia. Mean age of patients at transplant was 12.12 ± 5.16 years. All patients at transplant were in aplastic phase. Conditioning was done with fludarabine 120mg/m2, ATG 20 mg/kg and Cyclophosphamide at a dose of 20-40 mg/kg. Mean time to neutrophil engraftment was 12.3 ± 2.92days and for platelets 20 ± 10.3 days. Major post-transplant complications were neutropenic fever in 26 (96%), hypertension in 18 (66.6%), mucositis in 12 (44.4%), azotaemia in 8 (29.6%), gut toxicity in 7 (25.9%) and haemorrhagic cystitis in 5 (18.5%) patients. Four patients (14.8%) had acute graft versus host disease while 7 (26%) patients had chronic GVHD. Overall survival at 6 months, 1, 5 and 8 years was 67%, 63%, 59% and 55% respectively. While overall survival in patients transplanted at younger age (<11 years) was 81.8% compared to 37.5% in older age group (>11years) and was statistically significant (p-value = 0.03). Conclusion: Our study demonstrated survival difference in Fanconi anaemia patients when transplanted at younger age and conditioning with cyclophosphamide 30 mg/kg, fludarabine 120mg/m2 and thymoglobulin 10mg/kg as an acceptable conditioning protocol.